Surgical anatomy of superior gluteal artery in relation to lumbosacral plexus – A cadaveric study in the Indian population - Anjali Shastry; Anu Francis (Asian Journal of Medical Sciences, 2024)
Background: The superior gluteal artery (SGA) passes in between branches of the lumbosacral plexus after arising from the internal iliac artery. Variations in the course of SGA from the internal iliac artery till it passes out of the pelvis through the greater sciatic foramen are very important during pelvic surgeries. Pseudoaneurysm of SGA caused by iatrogenic injuries can compress branches of the lumbosacral plexus, causing foot drops and sciatica. Aims and Objectives: The aim is to study the course of the SGA in relation to branches of the lumbosacral plexus. Materials and Methods: A cross-sectional observational study was done on 25 formalin-fixed human adult cadavers. Dissections were performed in the pelvic region and branches of the internal iliac artery and lumbosacral plexus were identified. SGA was traced on both sides from origin till passing out of the greater sciatic foramen and its relation to branches of lumbosacral plexus was recorded. Results: Three types of pathways taken by SGA were identified in relation to the lumbosacral plexus. The most common path taken by the SGA was between the lumbosacral trunk (LST) and the first sacral nerve. Thirty-five out of 50 were of this type (70%). Ten out of 50 had the second most common type which was between L4 and L5 branches of LST (20%). Five cadavers had SGA lateral to LST (10%). Ten cadavers out of 25 (40%) had side differences in the type of course taken by SGA in relation to the lumbosacral plexus. Conclusion: A surgeon must keep in mind variations in the path taken by SGA in relation to the lumbosacral plexus to prevent pseudoaneurysms of SGA, which in turn can compress branches of lumbosacral plexus, causing foot drop and sciatica.